2018
DOI: 10.1039/c8sc01043a
|View full text |Cite|
|
Sign up to set email alerts
|

Polariton chemistry: controlling molecular dynamics with optical cavities

Abstract: Strong coupling of molecules with confined electromagnetic fields provides novel strategies to control chemical reactivity and spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
575
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 565 publications
(583 citation statements)
references
References 183 publications
(402 reference statements)
7
575
0
1
Order By: Relevance
“…Figure 1 demonstrates that the coupling with the radiation field leads to the formation of three 'bright' polaritonic surfaces, and as shown in the bottom left panel, N a − 1 'dark states'. Although these 'dark states' can affect excited state dynamics [35], they usually have no significant contribution to the spectrum [3,47]. With increasing atom number the effective coupling with the field increases and the polaritonic surfaces become more pronounced.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Figure 1 demonstrates that the coupling with the radiation field leads to the formation of three 'bright' polaritonic surfaces, and as shown in the bottom left panel, N a − 1 'dark states'. Although these 'dark states' can affect excited state dynamics [35], they usually have no significant contribution to the spectrum [3,47]. With increasing atom number the effective coupling with the field increases and the polaritonic surfaces become more pronounced.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Also, the effect on the kinetics has been observed to increase as the collective coupling intensifies, as a consequence of the large number of molecules present in a sample. 1 These observations are reminiscent of the description of light-matter coupling in terms of hybrid states known as polaritons, [7][8][9][10][11][12] which successfully explains the optical properties of these systems. [13][14][15][16][17] Recently, it has been suggested that a class of nonadiabatic charge transfer reactions would experience a catalytic effect from resonant collective coupling between high-frequency modes and infrared cavity modes; the mechanism relies on the formation of vibrational polaritons which feature reduced activation energies compared to the bare molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Describing the photon-matter interaction with the tool of cavity quantum electrodynamics is an emerging field. It has been successfully demonstrated both experimentally [26][27][28][29][30][31][32] and theoretically [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], that the quantized photonic mode description of the electromagnetic field can provide an alternative solution for studying adequately the light-molecule's OPEN ACCESS RECEIVED…”
mentioning
confidence: 99%